BOOMERanG - MASI S.; ADE P. A. R.; BALBI A.; BOCK J. J.; BOND J. R.; BORRILL J.; BOSCALERI A.; CABELLA P.; CONTALDI C. R.; CRILL B. P.; DE BERNARDIS P.; DE GASPERIS G.; et al. (Societa Astronomica Italiana / Florence:Largo E Fermi 5, 50125 Florence Italy:011 39 55 2752270, 2003)
he BOOMERanG experiment is a balloon-borne microwave telescope devoted to measurements of anisotropy and polarization of the Cosmic Microwave Background Radiation (CMB). The instrument is multiband in order to map the CMB and have a good understanding of all the important contaminating signals, (mainly galactic), and remove them if needed. Observations are carried out at about 38 Km of altitude, during a circum-antarctic Long Duration Balloon flight provided by NASA-NSBF. After two test flights in 1997, the instrument has been flown as a long duration payload in 1998 (covering four bands at 90, 150, 240, 410 GHz), and in 2003 (covering three bands at 150, 245, 345 GHz with polarization sensitive bolometers). Data from the first Antarctic flight are now fully analyzed; data analysis of the second (polarization) flight is currently under way.